Berberine Decreases Thrombosis Potential Induced by a High-choline Diet by Inhibiting CutC Enzyme - Qu, Hua; Zhang, Ying; Shi, Jun-he; Zhao, Yi-han; Gao, Jie; Gao, Zhu-ye; Shi, Da-zhuo (Current Medicinal Chemistry, 2024)
Introduction: Gut microbes influence thrombosis potential by generating trimethylamine N-oxide (TMAO). However, whether the antithrombotic effect of berberine is associated with TMAO generation remains unclear. Objective: The present study was designed to explore whether berberine decreases the TMAO-induced thrombosis potential and the possible mechanism underneath it. Methods: C57BL/6J female mice under a high-choline diet or standard diet were treated with/without berberine for 6 weeks. The TMAO level, carotid artery occlusion time following FeCl3 injury and platelet responsiveness were measured. The binding of berberine to the CutC enzyme was analysed with molecular docking, and molecular dynamics simulations were verified with enzyme activity assays. Results: The results showed that berberine increased the carotid artery occlusion time following FeCl3 injury and decreased the platelet hyperresponsiveness induced by a high- choline diet, both offset by intraperitoneal injection of TMAO. The effect of berberine on thrombosis potential was associated with decreasing the generation of TMAO by inhibiting the CutC enzyme. Conclusion: Targeting TMAO generation with berberine might be a promising therapy for ischaemic cardiac-cerebral vascular diseases.
Keywords: thrombosis potential gut